Efficacy of divozilimab in the treatment of systemic sclerosis: results of the randomized phase III clinical trial BCD-132-5/LIBERIUS - L. P. Ananyeva; M. N. Starovoytova; I. Z. Gaydukova; G. V. Lukina; E. V. Zonova; L. V. Eliseeva; G. F. Fatkhullina; D. I. Abdulganieva; D. G. Krechikova; T. V. Kropotina; O. B. Nesmeyanova; I. B. Vinogradova; et al. (Современная ревматология, 2025)
The search for new therapeutic options for the treatment of systemic sclerosis (SSc) is an urgent issue in rheumatology. The article presents the results of the double-blind, randomized, placebo-controlled phase III clinical trial BCD-132-5/LIBERIUS on the efficacy and safety of divozilimab (BCD-132) in the treatment of SSc.Objective: to investigate the efficacy and safety of divozilimab in patients with SSc compared to placebo.Material and methods. After enrolment in the study, patients received divozilimab or placebo for 48 weeks, after which they were switched to an open-label divozilimab therapy until week 96.Results and discussion. Divozilimab was superior to placebo regarding the primary endpoint change in mRSS at week 48 compared to baseline, and the therapy had a positive effect on respiratory function parameters. Divozilimab treatment was well tolerated.Conclusion. Thus, divosilimab may represent a new therapeutic option for patients with SSc.